The etiological profile and alterations in cerebrospinal fluid characteristics in patients with bacterial meningitis - O. O. Chernysheva; M. S. Potemkina; M. M. Gadzhikulieva; I. V. Davydova; T. Yu. Smirnova; I. Ch. Partilkhaeva; S. A. Shutko (Инфекция и иммунитет)
Currently, bacterial meningitis (BM) remains a form of life-threatening infectious pathology, with a mortality rate ranging from 4% to 35% and poor prognosis often accompanied by diverse specific and non-specific complications, including infectious toxic shock, cerebral edema, ventricular inflammation, hydrocephalus, acute cerebrovascular accidents, venous sinus thrombosis, disseminated intravascular coagulation (DIC) syndrome, respiratory distress syndrome (RDS) syndrome, inappropriate secretion of antidiuretic hormone, and systemic inflammatory response syndrome. In clinical practice, the early identification of the causative microorganism and the implementation of proper antibiotic treatment, as well as a comprehensive assessment of the patient’s status and management, are crucial for minimizing a risk of related severe complications and mortality. The BM etiology is characterized by a highly variable nature, contingent upon a multitude of factors such as geographic location, temporal context, patient age, immunological status, and other variables. Over the past two to three decades, advancements in conjugate vaccines and the use implementation of antibiotic treatment have brought about alterations in the spectrum of pathogens responsible for meningitis. The objective of this study was to delve into the etiological profile and prognostic implications of cerebrospinal fluid (CSF) parameters among patients with diagnosed meningitis admitted to the Neuroinfectious Diseases Division of the Infectious Clinical Hospital No. 2 (Moscow) between 2022 and 2023. A retrospective analysis of medical records of meningitis patients admitted to the Infectious Clinical Hospital No. 2 during 2022–2023 was conducted. The data were analyzed using the k-means clustering algorithm implemented in the Loginom analytics software to create a scenario, as well as OLAP cubes. The study involved the analysis of medical records for 110 patients aged 18–89 years old. Among the BM pathogens identified, Neisseria meningitidis emerged as the most prevalent in this patient cohort, accounting for 68.2% of cases. Within the group of meningococcal meningitis cases, serovariants A and W135 were the most frequently detected, accounting for 49.3% and 33.3%, respectively. Significant alterations in cerebrospinal fluid parameters, characterized by elevated cell counts and lowered glucose levels, were observed among patients with purulent meningitis resulting from serogroup A Neisseria meningitidis infections. A combination of elevated baseline cell level along with high concentrations of proteins, and lactate, coupled with the presence of D-dimer in cerebrospinal fluid, has been associated with a severe disease progression and the emergence of critical and life-threatening sequelae.